The impact of audit quality on operational efficiency of non-financial enterprises listed on the Vietnamese stock market in the period before and after COVID-19 - Hung, Dinh The; Nhi, Pham Lan; Long, Le Bao (The Economics and Finance Letters, 2025)
This research seeks to examine the effect of audit quality on the financial performance of non-financial listed firms in Vietnam during the period 2014–2023, with a sub-period analysis of pre- and post-COVID-19 outbreak. It considers major determinants of audit quality, including Big 4 auditors and audit rotation, as well as financial variables such as leverage, size, and industry type. The results indicate that companies audited by the Big 4 tend to have better financial performance, which is attributed to higher transparency and credibility in financial reporting. Nonetheless, the positive relationship was weakened during the COVID-19 period, as increased economic uncertainty limited the contribution of audit quality to maintaining firm value. Most importantly, the study concludes that audit rotation, measured by the frequency of auditor changes, has no statistically significant impact on financial performance. This suggests that the length of auditor rotation, within the current regulatory context, may not significantly affect audit quality and corporate performance. Furthermore, financial leverage consistently has a negative effect on firm value, highlighting the importance of effective capital structure management. These findings underscore the need to reinforce audit quality standards and reconsider audit rotation policies to enhance auditor independence, ensure continuity, and develop auditor expertise. Such measures are essential to promote greater financial transparency, restore investor confidence, and improve efficiency amid economic turmoil.